Exploring the Interplay of Smoking Behavior, Heart Rate Variability, Pulmonary Function Test Results, Diabetes, and Mood Disorders: A Systematic Review - Bipin Kumar; Tanuj Mathur; Yoshita R. Annepu; Krishna K. Annepu; Perugu D. K. Chaitanya (Journal of Pharmacy and Bioallied Sciences)
This systematic review aimed to collate and analyze findings from various studies that explored the associations between heart rate variability (HRV), smoking behavior, pulmonary function, diabetes, and mood disorders. A comprehensive database search strategy was employed, utilizing medical subject headings terms combined with Boolean operators across seven databases. The review found that conditions such as hypertension and type 2 diabetes exacerbate cardiac autonomic dysfunction, thereby aggravating cardiovascular risks. HRV emerged as a potential early indicator of cardiac morbidity in smokers, with immediate disruptions noted following acute smoking episodes. Furthermore, both pulmonary and cardiac autonomic functions were influenced by the autonomic control of cardiovascular function, independent of smoking status. The findings underscore the importance of HRV as a multifaceted indicator that reflects the health impacts of lifestyle choices, metabolic conditions, and mental health states.